2022
DOI: 10.3390/bioengineering9040162
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Tissue Bioengineering for the Treatment of Postsurgical Lymphedema

Abstract: Lymphedema is characterized by progressive and chronic tissue swelling and inflammation from local accumulation of interstitial fluid due to lymphatic injury or dysfunction. It is a debilitating condition that significantly impacts a patient’s quality of life, and has limited treatment options. With better understanding of the molecular mechanisms and pathophysiology of lymphedema and advances in tissue engineering technologies, lymphatic tissue bioengineering and regeneration have emerged as a potential thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 137 publications
0
7
0
Order By: Relevance
“…However, collagen deposition and vascular structures were observed around the hADSC injection site, and structures such as lymph node capsules were identified. Previous investigators have reported that hADSCs injection improved lymphedema in an animal model of lymphedema 7,20 . In our results, the effect of hADSCs injection was not significant.…”
Section: Discussionmentioning
confidence: 96%
“…However, collagen deposition and vascular structures were observed around the hADSC injection site, and structures such as lymph node capsules were identified. Previous investigators have reported that hADSCs injection improved lymphedema in an animal model of lymphedema 7,20 . In our results, the effect of hADSCs injection was not significant.…”
Section: Discussionmentioning
confidence: 96%
“…Foot and ankle volume are subjected to changes secondary to aerobic activities, lower-extremity trauma, or pathologic conditions [2,4]. The change following a surgical treatment is also important to consider [34], especially since the technique of the water basin, because of the wounds, is not suitable. The use of 3D optical scanners to track foot and ankle volume following surgery would also be an improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In both clinical and research contexts, it is critical to have a reliable and simple method for determining foot volume when it comes to evaluate peripheral edema or certain types of foot and ankle injuries [34] . While "pitting" in clinical settings and the use of a water Thus, our primary objective was to assess the reliability of a 3D portable scanner for obtaining volumetric measurements of the foot and ankle, in comparison with water volumetry, considered as the reference method.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 24 female and 5 male subjects were included (mean age 35.6 +/− 9.5 years, range 9-55). Self-declared shoe size was 38.17 +/− 3.23 (range [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Demographic characteristics are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In both clinical and research contexts, it is critical to have a reliable and simple method for determining foot volume when it comes to evaluating peripheral edema or certain types of foot and ankle injuries [34]. While "pitting" in clinical settings and the use of water volumetry or tape measurements (either ankle circumference or figure of eight) in research settings are considered the gold standard procedures, these techniques are prone to human error in measurements.…”
mentioning
confidence: 99%